1997
DOI: 10.1093/ajcn/65.2.459
|View full text |Cite
|
Sign up to set email alerts
|

n-3 fatty acids and urinary excretion of nitric oxide metabolites in humans

Abstract: Fish oils rich in n-3 fatty acids have been shown to augment endothelium-dependent vasodilation in human peripheral and coronary arteries. This suggests that n-3 fatty acids may enhance arterial nitric oxide production. To explore this hypothesis we measured total urinary nitrate output in healthy volunteers supplemented with a fish oil concentrate (FOC; n = 15) or purified eicosapentaenoic acid (EPA; n = 14) in a placebo-controlled, parallel-group study. The FOC contained 41% EPA and 23% docosahexaenoic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(44 citation statements)
references
References 66 publications
2
39
1
1
Order By: Relevance
“…DHA administration was proved to increase the release of endothelium-derived relaxing factor, presumably NO, which facilitates arterial relaxation, decreases blood pressure, improves vascularity, and consequently reduces the kidney function impairment. 17,54 Similar results were reported by Robinson and Stone, 20 who observed that DHA enhanced the formation of NO, which induces its hypotensive effect.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…DHA administration was proved to increase the release of endothelium-derived relaxing factor, presumably NO, which facilitates arterial relaxation, decreases blood pressure, improves vascularity, and consequently reduces the kidney function impairment. 17,54 Similar results were reported by Robinson and Stone, 20 who observed that DHA enhanced the formation of NO, which induces its hypotensive effect.…”
Section: Discussionsupporting
confidence: 77%
“…16 Polyunsaturated fatty acids are known to have potential cardiovascular benefits that include lowering blood pressure and improving vascular tone, whereas their impact on lipid peroxidation has been controversial. [17][18][19][20][21] In view of this, we investigated the ability of DHA to restore the deteriorated renal functions induced by CsA in a rat model. Furthermore, renal tissue nitric oxide (NO) level, lipid peroxidation, protein oxidation, and urinary level of NO were investigated in an attempt to understand the mechanistic basis of the observed DHA activities.…”
Section: Introductionmentioning
confidence: 99%
“…NO production (110) . In summary, there are too few data to conclude whether EPA and DHA have differing effects on endothelium-dependent vasodilation, but early indications are that DHA might be more effective in improving EF.…”
Section: Endothelial Functionmentioning
confidence: 99%
“…Vegetable oil rich in the n-6 FAs have been promoted as lowering blood cholesterol concentration of the people in USA (Hass, 1999). Harris (1997) showed that the plant n-3 FA caused rise of LDL-cholesterol by 5-10% and HDLcholesterol by 1-3%. Fickova et al (1998) noticed that rats fed on the diet containing n-3 FA contained significantly lower level serum triglycerides compared with those fed on diets having n-6 FAs.…”
Section: Lipid Profilementioning
confidence: 99%